2006
DOI: 10.1007/s11414-006-9025-3
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the BASIS-24© Mental Health Survey for Whites, African-Americans, and Latinos

Abstract: Increasing racial and ethnic diversity calls for mental health assessment instruments that are appropriate, reliable, and valid for the wide range of cultures that comprise the current US population. However, most assessment instruments have not been tested on diverse samples. This study assessed psychometric properties and sensitivity to change of the revised Behavior and Symptom Identification Scale (BASIS-24) among the three largest race/ethnicity groups in the USA: Whites, African-Americans, and Latinos. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 33 publications
1
75
0
Order By: Relevance
“…28 Parents completed an inventory of psychiatric symptoms, the Behavior and Symptom Identification Scale (BASIS), which is reliable and valid for Latinos. 29 An overall index of psychiatric symptoms was derived.…”
Section: Individual Parent Factorsmentioning
confidence: 99%
“…28 Parents completed an inventory of psychiatric symptoms, the Behavior and Symptom Identification Scale (BASIS), which is reliable and valid for Latinos. 29 An overall index of psychiatric symptoms was derived.…”
Section: Individual Parent Factorsmentioning
confidence: 99%
“…48 However, the 0.90 and 0.91 values obtained in the present study are consistent with those obtained by other efforts to validate instruments in minority populations and slightly better than those obtained for English-speaking Latinos who completed the BASIS-24 © in English. 16 For example, in a study of the Psychopathy Checklist Revised, Cooke et al 39 reported NNFI=0.88 and CFI=0.92 for African Americans. Research on cross-ethnic equivalence of the Center for Epidemiological Studies Depression Scale reported NNFI values of 0.92 for Mexican Americans but only 0.76 for CubanAmericans and 0.83 for Puerto Rican Americans.…”
Section: Discussionmentioning
confidence: 99%
“…33 Scoring the instrument Following confirmation of factor structure, a weighted scoring algorithm developed from the English instrument was used to obtain subscale and overall mean scores. 16 The weighted scoring algorithm is a linear approximation based on a graded response Item Response Theory model. 17 Assessing reliability and validity of the instrument Reliability and validity analyses were conducted separately for inpatient and outpatient samples.…”
Section: Data Analysis: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The first sample consisted of the subset of self-identified Latinos among a cohort of Englishspeaking inpatients and outpatients receiving mental health or substance abuse treatment at programs across the U.S. The BASIS-24 assessments were made at the start of the study, with data collected -2002(Eisen et al 2006. A total of 370 BASIS-24 assessments were available for our study.…”
Section: Application To a Mental Health Surveymentioning
confidence: 99%